2013
DOI: 10.4103/0189-6725.125429
|View full text |Cite
|
Sign up to set email alerts
|

Role of damage control enterostomy in management of children with peritonitis from acute intestinal disease

Abstract: Damage-control enterostomy is useful in management of severely ill children with intestinal perforation or gangrene. Careful and meticulous attention to fluid and electrolyte balance, and stoma care, especially in the first several days following surgery, are important in preventing morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…Complications related to the surrounding skin (including allergic dermatitis, faecal dermatitis and avulsion injury) are the most common and usually caused by improper nursing care. Therefore, experienced nursing staff and good nursing techniques are very important to reduce the incidence of complications and improve patient survival (Ameh, Ayeni, & Kache, ; Ciğdem, Onen, & Duran, ; Minaev et al, ; Sheikh, Akhtar, & Ahmed, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications related to the surrounding skin (including allergic dermatitis, faecal dermatitis and avulsion injury) are the most common and usually caused by improper nursing care. Therefore, experienced nursing staff and good nursing techniques are very important to reduce the incidence of complications and improve patient survival (Ameh, Ayeni, & Kache, ; Ciğdem, Onen, & Duran, ; Minaev et al, ; Sheikh, Akhtar, & Ahmed, ).…”
Section: Discussionmentioning
confidence: 99%
“…This variety makes it difficult for stoma caregivers to choose the best product to avoid damage to the skin surrounding of the stoma, ensure the quality of life of the patient and minimize the economic burden (O'Flynn, ). Some studies have reported that the proper use of orthostomy nursing products can reduce the risk of postoperative complications (Ameh et al, ). The choice of proper ostomy care products can avoid some of the problems associated with the skin around the colostomy (Burch, ; Rudoni & Dennis, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При этом проблемный участок тонкой кишки выводится на брюшную стенку в виде концевой либо петлевой илеостомы [9]. Подобная тактика может снизить смертность от перитонита и его последствий, однако формирование энтеростомы имеет свои осложнения (начиная от мацерации кожи по окружности стомы и заканчивая водно-электролитными нарушениями, приводящими к летальному исходу) [6]. Реконструк-тивные операции, предпринимаемые для ликвидации энтеростом и колостом, в 10 % случаев оканчиваются несостоятельностью сформированных анастомозов, при этом каждый десятый из этих пациентов уми-рает [10].…”
Section: Conclusion When One Forms the "End-to-end" Anastomosis In Tunclassified
“…Однако необоснованная резекция жизнеспособной кишки может стать причиной энтеральной недостаточности [9,10]. Если же оставить некротически измененную кишку, то это неизбежно приведет к развитию перитонита с последующей релапаротомией, дренированием брюшной полости и стомирующей операцией [11][12][13][14][15]. Таким образом, клинические способы определения жизнеспособности кишки, основанные на визуальной диагностике ишемического повреждения органа, не лишены субъективности, и ориентация только на них может привести к неправильной оценке витальных свойств органа [16,17].…”
unclassified